2003
DOI: 10.1007/s00268-002-6314-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Jejunal Interdigestive Migrating Motor Complex and Quality of Life after Total Gastrectomy with Roux‐en‐Y Reconstruction for Early Gastric Cancer

Abstract: A total of 22 patients (16 men, 6 women; age 33 to 70 years, m mean, 60.2 years) 1.0 to 1.5 years (mean 1 year and 2 months) after total gastrectomy with Roux‐en‐Y reconstruction for early gastric cancer (D2 lymph node dissection, curability A) were divided into two groups based on the occurrence of interdigestive migrating motor complex, phase III (IMMC‐pIII) from the Roux‐en‐Y loop, and postoperative quality of life (QOL) was compared. Results were as follows: (1) Patients in the IMMC‐ pIII positive group (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
0
15
0
3
Order By: Relevance
“…13,14 In Japan, RY after TG has been commonly performed for the treatment of gastric cancer because of its technical simplicity and safety. 1,15,16 However, there have been some problems in patients who have undergone conventional TG with RY. Namely, the lack of LES with a His angle and gastric reservoir function after TG decreases the dietary intake status reduces appetite and causes ARE and EDS, which markedly impairs QOL and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13,14 In Japan, RY after TG has been commonly performed for the treatment of gastric cancer because of its technical simplicity and safety. 1,15,16 However, there have been some problems in patients who have undergone conventional TG with RY. Namely, the lack of LES with a His angle and gastric reservoir function after TG decreases the dietary intake status reduces appetite and causes ARE and EDS, which markedly impairs QOL and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…ARE and EDS were noted in approximately 10~20 per cent of patients after RY reconstruction. 1,15,16 First, to prevent ARE, we performed LES preservation and His angle formation in patients after 17 We previously suggested that LES-preserving RY could not prevent ARE completely. 7 Therefore, we preserved the abdominal oesophagus at the His angle level with the longitudinal axis of the oesophagus and added a new His angle formation using a jejunal J pouch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMCs reoccur in the proximal small intestine within 3 h after the surgery but initially with a quicker cycle time and reduced Phase II activity (Benson et al, 1994; Husebye, 1999). Interesting, patients undergoing gastrectomy for gastric cancer who then had Roux-en-Y reconstruction (the stomach is removed and to achieve continuity to the intestine the proximal jejunum is divided and the aboral jejunum anastomosed to the esophagus – the divided oral part of the jejunum is reconnected to the jejunum distal to the esophageal anastomosis so bile and pancreatic secretions can be directed into the jejunum and the shape of a Y is created), could be divided into those with intestinal MMC activity and those without (Tomita et al, 2003). Compared to the latter, patients with phase III MMC activity tended to have more appetite and greater food intake, as well as fewer symptoms associated with dumping, reflux, nausea or lower bowel symptoms.…”
Section: Dysregulation Of the Hungry Human Stomachmentioning
confidence: 99%